A VIDEO PRODUCTION THESIS ON ORGAN DONATION AND TRANSPLANTATION ( March 2007) - Bamba, Edwin b.; Dela Cruz, Jan Viktor Y.; Lagrana, Glenda Marie L.; Ravara, Pawlo Marc S. and Reyes, Jocelyn V. 4 0 16; 5 (2007)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2007.;Bachelor of Science in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2